Cerebral Dominance for Language in Literates and Illiterates - Kumar PJ (Journal of All India Institute of Speech and Hearing, 1970)
Cameron, Currier and Haerer (1971) studied 65 patients who had  left hemisphere damage in order  to see whether there existed a relationship between  literacy  and language disturbances in these  patients. They  reported more language disturbances in literates and semi-literates than with the illiterates. Seventy  eight  per cent of  their literate group and sixty  four per cent of their semiliterate group exhibited language disturbances with the left hemisphere damage. Only  thirty  six per cent of their illiterate group had language  disturbances.